Diffusion of artificial intelligence across Indonesia: Digital disparities, local contexts, and policy implications - Aziz, Muhajir Sulthonul; Subiakto, Henri; Puspa, Ratih (Masyarakat, Kebudayaan dan Politik, 2025)
Digital literacy across the urban–rural divide in Indonesia plays a significant role in the adoption/implementation of AI. This study attempts to investigate the principal factors behind AI introduction within a descriptive qualitative study and collaborative case study design. The current study is qualitative, using semi-structured interviews with 180 informants conducted in 36 communities from eight key islands during the period of October to December 2024. The findings indicate that rural areas lag behind urban areas in terms of infrastructure, digital literacy readiness and perceived technological complexity, whereas urban areas benefit from the vibrant ecosystems, institutional support as well as accumulation of training programs. Any vision for digital transformation should be joined up and include increased infrastructure investment, investment in community based digital literacy programs as well as development of AI applications that are locally relevant and culturally sensitive. These results elaborate on the Diffusion of Innovations Theory as articulated by Rogers, showing how infrastructural and sociocultural contexts interact in the adoption of technology, while also offering new perspectives for policy and practice in contrasting low and middle-income contexts.